Ultrafast Broadband Nonlinear Optical Response in Co-Doped Sb2Se3 Nanofilms at Near-Infrared - Sun, Di; Fang, Yu; Yan, Xiaoyan; Shan, Wen; Sun, Wenjun; Meng, Qingyu (Frontiers in Materials, 2021)
Transition Metal-doped Sb2Se3 has become a heated topic caused by the strong nonlinear optical response and ultrafast response time at the high laser excitation. In this paper, the Co-doped Sb2Se3 with different doping amounts (0.5 W, 1.0 W, and 1.5 W) nanofilms are prepared by magnetron sputtering technology, and the nonlinear absorption and refraction behavior of Co-doped Sb2Se3 nanofilms at near-infrared is systematically studied. The results of the femtosecond (fs) Z-Scan experiment indicate that the Co-doped Sb2Se3 nanofilms exhibit the broadband nonlinear response properties owing to the free carrier absorption (FCA), the Kerr refraction, the two-photon absorption (TPA) and the free carrier refraction (FCR). The nonlinear absorption coefficients of Co-doped Sb2Se3 nanofilms are from 3.0×10-14 cm/MW to 2.03×10-13 cm/MW under the excitation at 800 nm, 980 nm, and 1030 nm. Otherwise, the nonlinear refractive index of the Co-doped Sb2Se3 nanofilms is from 4.0×10-19 cm2/MW to -3.89×10-18 cm2/MW at 800 nm, 980 nm, and 1030 nm. More importantly, Co-doped Sb2Se3 (1.5 W) nanofilm exhibits ultrafast carrier absorption (<1 ps). Furthermore, the crystalline degree and the consistency of the Co-doped Sb2Se3 nanofilms have a corresponding increase owing to the increase of Co dopant content. Moreover, the Co-doped Sb2Se3 nanofilms have a stronger transient absorption intensity of ΔOD>6.3 in the fs transient absorption experiment. Furthermore, the Co doping content can controllably tune the ultrafast carrier absorption, the intensity of the reverse saturation absorption, broadband nonlinear optical response and carrier relaxation time of Co-doped Sb2Se3 nanofilms. These results are sufficient to support their applications in broadband nonlinear photonic devices.